Reaction Of Chilli Genotypes And Breeding Lines Against Leveillula Taurica Inciting Powdery Mildew (Journal of Plant Disease Sciences, 2018)
Chilli (Capsicum annuum L.) also called as hot pepper is an important spice cum vegetable crop. India is the major producer, consumer and exporter of chilli in the world. India contributes about 25 per cent of total world production. Andhra Pradesh is the largest producer of chilli occupying 27 per cent followed by Karnataka (19%) and Maharashtra (12%) (Chandra et al., 2009). Virtually chilli is grown in wide range of climatic conditions from almost the sea level up to an altitude of 1500 meters in tropical and sub- tropical regions. Chilli suffers from many diseases caused by fungi, bacteria, and viruses. Fifty one different pathogens have been recorded to cause diseases on the various plant parts of chilli. Among the various diseases of chilli, powdery mildew incited by Leveillula taurica is one of the dreaded disease known to causes significant yield losses upto 24 % (Sharmila et al., 2004). The disease is characterized by yellowing of the upper surface of the foliage with a whitish mycelial powdery mass on the corresponding lower surface. In severe cases whitish mass develops on both the surfaces which resulted in premature defoliation (Jharia et al., l978). Heavy infection leads to shedding of leaves and flower buds resulting in heavy yield losses due to reduction in size and number of fruits. Many systemic and non-systemic fungicides were reported to be effective for management of powdery mildew of chilli (Amresh et al., 2016). However, breeding for resistance is essential to minimize fungicide usage as the crop is extensively used as vegetable in the form of green chilli also. The present investigation was therefore carried out to find out resistant sources of chilli crop to L. taurica so as to use in further breeding programmes.
Keywords: Powdery mildew; chilli; esistance genotypes